Perlindungan Transformasi Karya Cipta Lontar Dalam Bentuk Digitalisasi - Dian Sawitri, Dewa Ayu; Dharmawan, Ni Ketut Supasti (Acta Comitas, 2020)
The purpose of this study to examine the protection of transformation of lontar copyrighted works in the form of digitalization and the mechanism of legalizing the transformation of works that were originally in the form of lontar. This study uses a socio-legal researchy method which is a mixture of normative legal research methods with empirical legal research methods. This study uses a statutory approachy, conceptuayl approach and facts. The study results show that the regulation of transformation of lontar copyright works in the form of digitalization is regulatedd in Article 40 paragraph 1 letter n of the Copyright Law which is made possible through an expanded interpretation. It can be stated that the transformation also includes works of traditional cultural expression. The process of legalizing the transformation is included in Article 26 paragraph (1) of the Cultural Promotion Act which explains that the Central Government and the Regional Government are obliged to save the Cultural Promotion Object. Transformation of lontar into the form of digitization is one form of saving against lontar but in the process of this transformation must still refer to the agreement of the owner of the lontar work.  Tujuan studi ini untuk mengkaji perlindungan transformasi karya cipta lontar dalam bentuk digitalisasi serta mekanisme legalisasi pentransformasian dari karya yang awalnya berbentuk lontar. Studi ini menggunakan metode penelitian sosio-legal yang merupakan campuran dari metode penelitian hukum normatif dengan metode penelitian hukum empiris. Studi ini menggunakan pendekatan perundang-undangan, pendekatan konseptual dan fakta. Hasil studi menunjukkan bahwa pengaturan transformasi karya cipta lontar dalam bentuk digitalisasi diatur dalam Pasal 40 ayat 1 huruf n UU Hak Cipta yang dimungkinkan melalui suatu penafsiran yang diperluas dapat dikemukakan bahwa transformasi juga mencakup karya ekspresi budaya tradisional. Proses legalisasi transformasi termasuk dalam Pasal 26 ayat 1 Undang-Undang Pemajuan Kebudayaan yang menjelaskan bahwa Pemerintah Pusat danjatau Pemerintah Daerah penyelamatan dilakukan wajib Objek Pemajuan Kebudayaan. Transformasi lontar ke dalam bentuk digitalisasi merupakan salah satu bentuk penyelamatan terhadap lontar tetapi dalam proses transformasi ini harus tetap